Reassessment of osteoporosis-related femoral fractures and economic burden in Saudi Arabia. Issue 1 (December 2015) - Sadat-Ali, Mir; Al-Dakheel, Dakheel; Azam, Md; Al-Bluwi, Mohammed; Al-Farhan, Mohammed; AlAmer, Hussein; Al-Meer, Zakaria; Al-Mohimeed, Abdallah; Tabash, Ibrahim; Karry, Maher; Rassasy, Yaseen; Baragaba, Mohammed; et al.
Abstract Summary The current study reassesses the prevalence of fragility fractures and lifetime costs in the Eastern Province of Saudi Arabia. Forty-two percent (391) of the fractures were at the neck of the femur, and 38.6 % (354) were inter-trochanteric fractures. The overall incidence was assessed to be 7528 (1, 300, 336 population 55 years or older) with the direct cost of SR564.75 million (150.60 million). A National Fracture Registry and osteoporosis awareness programs are recommended. Purpose Proximal femur fragility fractures are reported to be increasing worldwide due to increased life expectancy. The current study is carried out to assess the incidence of such fractures in the Eastern Province of Saudi Arabia and to assess the costs incurred in managing them annually. Finally, by extrapolating the data, the study can calculate the overall economic burden in Saudi Arabia. Methods The data of fragility proximal femur fractures was collected from 24 of 28 hospitals in the Eastern Province. The data included age, sex, mode of injury, type of fracture, prescribed drug (and its cost), and length of hospital stay. Population statistics were obtained from the Department of Statistics of the Saudi Arabian government Web site. Results Twenty-four hospitals (85 %) participated in the study. A total of 780 fractures were sustained by 681 patients. Length of stay in the hospital averaged 23.28 ± 13.08 days. The projected fracture rate from all the hospitals would be 917 (an incidence of 5.81/1000), with a total cost of SR68.77 million. Further extrapolation showed that the overall incidence could be 7528 (1, 300, 336 population 55 years or older) with the direct cost of SR564.75 million (150.60 million). Conclusions Osteoporosis-related femoral fractures in Saudi Arabia are significant causes of morbidity besides incurring economic burden. We believe that a National Fracture Registry needs to be established, and osteoporosis awareness programs should be instituted in every part of Saudi Arabia so that these patients can be diagnosed early and treated appropriately to reduce both the number of fractures and the economic burden of the fractures.